EFFICACY OF FIRST AVAILABLE DIRECT-ACTING ANTIVIRAL AGENT IN TREATMENT OF CHRONIC HEPATITIS C; RESULTS FROM A SINGLE CENTRE IN PAKISTAN - Khan, Arif Qayyum; Mansoor, Hala; Raja, Javed Iqbal; Shahbaz, Raja Yasser; Fida, Samina; Siddique, Muhammad (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the efficacy of dual (sofosbuvir and ribavirin) and triple therapy (sofosbuvir ribavirinpegylated interferon) for treatment of hepatitis C. Study Design: Comparative cross sectional study. Place and Duration of Study: Department of Medicine, Combined Military Hospital, Lahore, from Nov 2014 to Mar 2017. Methodology: A total of 182 consecutive patients with age ≥18 years and positive HCV RNA by polymerase chain reaction were included, while patients with haemoglobin of <10 g/dl, albumin <2 g/dl, platelet count of <100/uL, creatinine clearance of <60 mL/min or liver disease caused by non-hepatitis C related causes were excluded from study. Results: Total 129 (70.8%) were treated with dual and 53 (29.1%) with triple therapy. Amongst patients with genotype 3 (158/182), the overall sustained virological response at 12 weeks (SVR 12) was 94.4% in patients with dual therapy while it was 97.3% with triple therapy. In non-cirrhotic patients it was 95% in treatment naïve and 100% in treatment experienced group. While in cirrhotic patients with genotype 3, SVR 12 with dual therapy was 83.3% (p=0.331) and 88.9% in treatment naïve and treatment experienced patients respectively, while it was 100% in both groups with triple therapy. SVR 12 for genotype 1 (21/182) was 100%, both for dual as well as for triple therapy. Haematological side effects dominated the clinical picture with 11.5% suffering from anaemia. Conclusion: Both dual and triple therapy were effective in patients with hepatitis C with acceptable level of side effects, genotype 3 being the most predominant genotype.